Public acceptance and preference towards rainwater harvesting in Klang Valley, Malaysia / Shahariah Asmuni … [et al.] - Asmuni, Shahariah; Baah, Ruzita; Yusoff, Sabariah; Ahmad Ridzuan, Fatin Nabilah Sofea (Universiti Teknologi Mara Selangor, 2016)
This study explored the public acceptance and preference towards rainwater harvesting (RWH) in the area of Klang Valley. Self-administered questionnaires were used to obtain data from 109 respondents. An interview was also conducted on an individual representing a household with a RWH system. Respondents generally accepted that rainwater could be collected and reused for non-potable uses such as washing the porch and vehicles and watering the garden. While suggested WTP values of non-owners of the system fall below RM500, actual interview showed a homeowner spending a much higher amount for the system’s installation. Among the attributes of a RWH system preferred by respondents were affordability, safety and convenience. Added feature of a system preferred would be having a unit subsidized by the government. These findings may assist policymakers in finding ways to promote the development and use of RWH systems in the country.